The contribution of HLA genes to IBD susceptibility and phenotype. - Yap, L; Ahmad, T; Jewell, D (2004)
The human leukocyte antigen (HLA) region located on chromosome 6p encodes the highly polymorphic, classical class I and II genes essential for normal lymphocyte function; it also encodes a further 224 genes. Many early studies investigating this region were limited by small sample size, poor statistical methodology, population stratification and variable disease definition. Although more recent studies have improved study design, investigators are still challenged by the complex patterns of linkage disequilibrium across this gene-dense region, and by the disease heterogeneity characteristic of all genetically complex disorders. However, a number of important observations have emerged from recent studies: (1) the HLA harbours gene(s) that determine susceptibility to colonic inflammation in both ulcerative colitis (UC) and Crohn's disease (CD); (2) most of the specific associations with UC and CD appear to differ; (3) associations between different ethnic groups differ; (4) markers in the HLA might predict the course of disease and the development of complications, notably the extraintestinal manifestations of disease.